Pelatihan Budikdamber Lele dan Kangkung di Semangga Jaya Merauke - Amir, Astaman; Widijastuti, Rosmala; Panga, Nurhaya; Sembiring, Ade; Ginting, Nina Maksimiliana (MALLOMO: Journal of Community Service, 2023)
Food security does not only talk about aspects of availability. Holistic food security concerns aspects of food availability, distribution, consumption, and security. In the context of the Semangga District, especially Semangga Jaya Village, food security is more related to the aspect of food security. This activity aims to improve community food security, especially in the Al Jannah Study Group through the production of safe food without pesticide contamination. In this program, we train and assist the community in Semangga Jaya Village, especially the Al Jannah study group. This service activity will include training, demonstrations on making Budikdamber, mentoring, and providing assistance for 4 Budikdamber technology packages so that they can be used sustainably by the community. The output target of this Community Partnership Service program is to increase knowledge, especially the Al Jannah study group in Semangga Jaya Village. This increase in knowledge will be measured using a questionnaire given before and after the training is carried out. Another output is the availability of vegetables and fish from Budikdamber which can be consumed or sold by the community which can increase food security.